Ayres Sensory Integration® for Addressing Play in Autistic Children: A Multiple-Baseline Examination. - Kuhaneck, Heather M.; Watling, Renee; Glennon, Tara J. (American Journal of Occupational Therapy)
Importance: Play is an area of difficulty for autistic children, and occupational therapy practitioners need evidence to guide interventions to improve play for this population. Ayres Sensory Integration® (ASI) intervention has not yet been studied for its impact on play outcomes. Objective: To examine the impact of ASI intervention on play types in autistic children. Design: Nonconcurrent, multiple-baseline design across subjects. Setting: Outpatient occupational therapy clinic in New England. Participants: Three autistic children, ages 5, 6, and 6 yr. Intervention: Twenty-four ASI sessions. Outcomes and Measures: Frequency of play type was coded using partial interval coding. Progress monitoring used Goal Attainment Scaling. Results: All three participants demonstrated changes in the frequency of specific types of play, but changes varied among them. Conclusions and Relevance: Findings suggest that ASI intervention may alter a child's patterns of play. What This Article Adds: This study is the first to examine the impact of ASI on play and the third that documents the feasibility of single-subject research for studying ASI. If confirmed in future studies, ASI could become an evidence-based intervention for improving play, an important outcome for autistic children and the profession of occupational therapy. Positionality Statement: This article uses the identity-first language autistic people. This nonableist language describes their strengths and abilities and is a conscious decision. This language is favored by autistic communities and self-advocates and has been adopted by health care professionals and researchers (Bottema-Beutel et al., 2021; Kenny et al., 2016). This study is the first to examine the impact of the Ayres Sensory Integration® (ASI) intervention on play outcomes for autistic children and the third study to document the feasibility of single-subject research for studying ASI.